PENGARUH SOCIAL MEDIA MARKETING DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (STUDI PADA PELANGGAN TOKOPEDIA DI KOTA SEMARANG) - Zuhad, Muhammad Daniel; Yoestini, Yoestini (Diponegoro Journal of Management, 2023)
ABSTRACT The research aims to examine the influence of social media marketing and brand image on purchase decisions, with purchase intention acting as an intervening variable. The study focuses on Tokopedia customers in Semarang City, specifically targeting customers aged between 18 and 30. The sample used amounted to 120 respondents. The data collection method uses a questionnaire with the Structural Equation Modeling (SEM) analysis technique using AMOS 24.0 as an analytical tool. The results showed social media marketing had a positive and significant effect on purchase intention, brand image had a positive and significant effect on purchase intention, social media marketing does not have a significant effect on purchase decisions, brand image does not have a significant effect on purchase decisions,, purchase intention had a positive and significant effect on purchase decision and both social media marketing and brand image have a significant effect influence on purchase indicates that purchase intention acts as a intervening variable